Controls on dryland mountain landscape development along the NW Saharan desert margin: Insights from Quaternary river terrace sequences (Dadès River, south-central High Atlas, Morocco). (15th June 2017) - Stokes, M.; Mather, A.E.; Belfoul, M.; Faik, F.; Bouzid, S.; Geach, M.R.; Cunha, P.P.; Boulton, S.J.; Thiel, C.
Abstract: This study documents river terraces from upstream reaches of the Dadès River, a major fluvial system draining the south-central High Atlas Mountains. Terraces occur as straths with bedrock bases positioned at 10 m altitudinal intervals up to 40 m (T1-T5) above the valley floor, becoming less common between 50 and 140 m. The rock strength, stratigraphy and structure of the mountain belt influences terrace distribution. Terraces are absent in river gorges of structurally thickened limestone; whilst well-developed, laterally continuous terraces (T1-T4) form along wide valleys occupying syncline structures dominated by weaker interbedded limestone-mudstone. Terrace staircases develop in confined canyons associated with weaker lithologies and influence from structural dip and stratigraphic configuration. Terraces comprise a bedrock erosion surface overlain by fluvial conglomerates, rare overbank sands and colluvium. This sequence with some OSL/IRSL age control, suggests terrace formation over a 100 ka climate cycle with valley floor aggradation during full glacials and incision during glacial-interglacial transitions. This integrates with other archives (e.g. lakes, glaciers, dunes), appearing typical of landscape development along the NW Saharan margin south of the High Atlas, and similar to patterns in the western-southern Mediterranean. The 100 ka climate cycle relationship suggests that the terrace sequence documents Late-Middle Pleistocene landscape development. Consistent altitudinal spacing of terraces and their distribution throughout the orogen suggests sustained base-level lowering linked to uplift-exhumation of the High Atlas. Low incision rates (<0.2 mm a −1 ) and general absence of terrace deformation suggests dominance of isostatically driven base-level lowering with relief generation being Early Pleistocene or older. Highlights: Dadès River terraces mapped along a 60 km upstream dryland mountain reach. Terrace distribution controlled by orogen rock strength, structure and stratigraphy. Terraces form over multiple 100 ka climate cycles throughout Early-Late Pleistocene. Low incision rates suggest regional isostatic-related base-level lowering. Terraces imply High Atlas relief generation is Pliocene-Early Pleistocene or older.